AUTOCHTHONOUS PHONOLOGICAL INFLUENCES IN SECOND LANGUAGE LEARNING, REMEDIAL STRATEGIES, AND RECOMMENDATIONS FOR COLLEGE STUDENTS - R, Shanmugasundaram; A, Noble Jebakumar (International Journal of Research -GRANTHAALAYAH, 2024)
Students in ESL classrooms come from a variety of L1 backgrounds and have varying pronunciation issues, thus often teachers are reluctant to teach pronunciation. This Teaching Tip report describes what are ways to give Remedial strategies to the Tamil speaking students in and around Kovilpatti Thoothukudi District, Tamilnadu. The study will involve the selection of a group of college students. The initial step is to identify their phonotactical concerns by observation and interviewing, and then add the usual errors that Tamil learners generally make. Through the curriculum created, they will receive the instruction required to overcome the effects and limitations. This paper explores Phonological problems in L2 acquisition, Discusses Common problems in Classroom. Experience has shown that Elucidate Phonetical basic patterns and Errors For instance, for a beginner learning Tamil, it would be challenging to distinguish between the following words: (Principle – Principaal, Gad – Guard, adopt – adapt). Unearthing the common mistakes made by students of this region. There will be ideas for additional study and instructional advice included with the recommendations.